"Research findings and daily teaching practice are worlds apart" – Predictors and consequences of scepticism toward the relevance of scientific content for teaching practice. (January 2023) - Nägel, Luisa; Bleck, Victoria; Lipowsky, Frank
Abstract: Research shows that beliefs such as scepticism toward the relevance of scientific content can hinder teachers' evidence-based practices. Despite this consequence of scepticism, little is known about its predictors. Therefore, we first analysed the relationship between scepticism toward the relevance of scientific content and preferred information sources with a sample of 332 teachers: Scepticism led to a lower preference for scientific sources. Second, we examined characteristics of professional competence as possible predictors of scepticism. We found that scepticism was lower among enthusiastic teachers, but it was higher when teachers believed in inborn teaching competences or were low academic achievers.